Prevalence and Risk Factors of Human Herpes Virus Type 8 (HHV-8), Human Immunodeficiency Virus-1 (HIV-1), and Syphilis among Female Sex Workers in Malindi, Kenya - M. M. Nzivo; R. M. Lwembe; E. O. Odari; J. M. Kang’ethe; N. L. M. Budambula (Interdisciplinary Perspectives on Infectious Diseases)
The prevalence of Human Herpes Virus type 8 (HHV-8), Human Immunodeficiency virus (HIV), and syphilis is high in Sub-Saharan Africa. Studies on HHV-8 in Kenya are few and data on its coinfection with HIV and syphilis scanty. This cross-sectional study among female sex workers (FSWs) in Malindi, Kenya, aimed to determine the prevalence of HHV-8, HIV, and syphilis mono/coinfections and identify associated risk factors. A total of 268 FSWs consented and were administered a structured questionnaire and screened for antibodies against HHV-8, HIV, and syphilis following the National Guidelines. FSWs positive for HHV-8 were 67/268 (25%), HIV 44/268 (16.4%), and 6/268 (2.24%) for syphilis. Eight out of 67 (12%) tested positive for HHV-8/HIV and 2/67 (3%) for HHV-8/syphilis coinfections. Married FSWs had higher odds of HHV-8 infection (OR 2.90, 95%, and P=0.043). Single marital status was inversely associated (OR 0.46, 95% CI 0.23-0.94, and P=0.034) with HIV infection. HIV was associated with increasing age (OR 14.79, P<0.001), inconsistent condom use (OR 2.69, P=0.004), increased duration as sex worker ≥6 (OR 3.0, P=0.002) and clients ≥4 (OR 4.0, P<0.001), intravenous drug use (OR 2.5, P=0.043), and early sex debut (P=0.049) unlike HHV-8 which was not associated with high risk sexual behavior. HHV-8/HIV coinfection was associated with increasing age (OR 11.21, P=0.027). Infection by HHV-8 was not significantly associated with HIV (OR 0.62; P=0.257) or syphilis (OR 1.52; P=0.636). There was a high likelihood of infection with HHV-8 compared to HIV (OR 8.6, P=0.014) and syphilis (OR 14.6, P<0.001). The lack of association of HHV-8 with high risk sexual behavior suggests that sexual transmission may not play a significant role in transmission of HHV-8 among FSWs in Malindi.